Platelet-Rich Fibrin Facilitates One-Stage Cartilage Repair by Promoting Chondrocytes Viability, Migration, and Matrix Synthesis - Wong, Chin-Chean; Ou, Keng-Liang; Lin, Yun-Ho; Lin, Ming-Fang; Yang, Tsung-Lin; Chen, Chih-Hwa; Chan, Wing P. (International Journal of Molecular Sciences, 2020)
The main aim of this study is to develop a one-stage method to combine platelet-rich fibrin (PRF) and autologous cartilage autografts for porcine articular cartilage repair. The porcine chondrocytes were treated with different concentrations of PRF-conditioned media and were evaluated for their cell viability and extracellular glycosaminoglycan (GAG) synthesis during six day cultivation. The chemotactic effects of PRF on chondrocytes on undigested cartilage autografts were revealed in explant cultures. For the in vivo part, porcine chondral defects were created at the medial femoral condyles of which were (1) left untreated, (2) implanted with PRF combined with hand-diced cartilage grafts, or (3) implanted with PRF combined with device-diced cartilage grafts. After six months, gross grades, histological, and immunohistochemical analyses were compared. The results showed that PRF promotes the viability and GAG expression of the cultured chondrocytes. Additionally, the PRF-conditioned media induce significant cellular migration and outgrowth of chondrocytes from undigested cartilage grafts. In the in vivo study, gross grading and histological scores showed significantly better outcomes in the treatment groups as compared with controls. Moreover, both treatment groups showed significantly more type II collagen staining and minimal type I collagen staining as compared with controls, indicating more hyaline-like cartilage and less fibrous tissue. In conclusion, PRF enhances the viability, differentiation, and migration of chondrocytes, thus, showing an appealing capacity for cartilage repair. The data altogether provide evidences to confirm the feasibility of a one-stage, culture-free method of combining PRF and cartilage autografts for repairing articular cartilage defects. From translational standpoints, these advantages benefit clinical applications by simplifying and potentiating the efficacy of cartilage autograft transplants.